2014
DOI: 10.1007/s12033-014-9754-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Horsegram (Macrotyloma uniflorum Lam.Verdc.) NAC Transcriptional Factor (MuNAC4) in Groundnut Confers Enhanced Drought Tolerance

Abstract: The NAC family being the largest plant-specific transcription factors functions in diverse and vital physiological processes during development. NAC proteins are known to be crucial in imparting tolerance to plants against abiotic stresses, such as drought and salinity, but the functions of most of them are still elusive. In this study, we report for the first time expression of the MuNAC4, a member of NAC transcription factor from horsegram (Macrotyloma uniflorum) conferring drought tolerance. The groundnut (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 54 publications
5
31
1
Order By: Relevance
“…This ultimately builds up a better survival capacity in T under higher salinity stress conditions, as also reported by Khare et al (2010) and Rai et al (2013). Likewise, in transgenic MuNAC4 peanut (Pandurangaiah et al 2014) and AtDREB1A peanut (Bhatnagar et al 2009), mtlD tomato (Khare et al 2010) and in some peanut cultivars (Chakraborty et al 2015), enhanced SOD, CAT, and POD activities were reported in response to various abiotic stresses. Besides, even exogenous application of mannitol is also reported to enhance the antioxidative enzymes activity of metal-induced oxidative stress tolerance in wheat (Adrees et al 2015).…”
Section: Relative Water Content (Rwc)supporting
confidence: 73%
See 1 more Smart Citation
“…This ultimately builds up a better survival capacity in T under higher salinity stress conditions, as also reported by Khare et al (2010) and Rai et al (2013). Likewise, in transgenic MuNAC4 peanut (Pandurangaiah et al 2014) and AtDREB1A peanut (Bhatnagar et al 2009), mtlD tomato (Khare et al 2010) and in some peanut cultivars (Chakraborty et al 2015), enhanced SOD, CAT, and POD activities were reported in response to various abiotic stresses. Besides, even exogenous application of mannitol is also reported to enhance the antioxidative enzymes activity of metal-induced oxidative stress tolerance in wheat (Adrees et al 2015).…”
Section: Relative Water Content (Rwc)supporting
confidence: 73%
“…3a, b) compared to other lines at all growth stages, indicating its relatively better ability for salinity stress tolerance. Significantly peanut (Pandurangaiah et al 2014) during abiotic stress imposition. All these suggest that T peanut lines having mtlD gene were less affected by oxidative stress than their WT counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…In soybean, GmNAC20 and GmNAC11 are involved in different abiotic stresses, and their expression in Arabidopsis conferred both salt and freezing tolerance (Hao et al, 2011). Overexpression of horsegram MuNAC4 in transgenic groundnut plants reduces the damage to membrane structures and enhances osmotic adjustment and antioxidative enzyme regulation under drought stress (Pandurangaiah et al, 2014). TaNAC29 and TaNAC67 are up-regulated under different abiotic stresses, and transgenic Arabidopsis plants expressing these genes showed increased salt and drought tolerance (Mao et al, 2014; Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The transgenic plants possessed efficient anti oxidative machinery which protected the plant cells from ROS induced oxidative damage. In other studies also increase in level of oxidative markers were reported when heterologous genes expressed in groundnut such as AtNHX (Asif et al, 2011), PHD45 (Manjulatha et al, 2014), AtNAC2 (Patil et al, 2014), MuNAC4 (Pandurangaiah et al, 2014). …”
Section: Discussionmentioning
confidence: 88%
“…The genes from Salicornia brachiata, ascorbate peroxidase ( SbAPX ), and abscisic acid stress ripening ( SbASR ) genes when expressed in groundnut displayed salt and drought stress tolerance coupled with more chlorophyll retention and enhanced levels of relative water content under normal/stress conditions (Singh et al, 2014; Tiwari et al, 2015). The transcription factors from Arabidopsis, AtNAC2 (Patil et al, 2014), AtDREB1A (Sarkar et al, 2014, 2016) and horsegram, MuNAC4 (Pandurangaiah et al, 2014) were exhibited drought and salt stress tolerance in groundnut by reducing the membrane damage and improving scavenging of reactive oxygen species scavenging (ROS). Groundnut transgenic plants ( cv TMV-2) simultaneously expressing three TFs ( AtDREB2A, AtHB7 , and AtABF3 ) displayed to increase drought, salinity, and oxidative stress tolerance compared to wild type (Pruthvi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%